1997
DOI: 10.1111/j.1469-7793.1997.449bk.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemo‐mechanical energy transduction in relation to myosin isoform composition in skeletal muscle fibres of the rat

Abstract: ATP consumption and force development were determined in single skinned muscle fibres of the rat at 12 °C. Myofibrillar ATPase consumption was measured photometrically from NADH oxidation which was coupled to ATP hydrolysis. Myosin heavy chain (MHC) and light chain (MLC) isoforms were identified by gel electrophoresis. Slow fibres (n= 14) containing MHCI and fast fibres (n= 18) containing MHCIIB were compared. Maximum shortening velocity was 1.02 ± 0.63 and 3.05 ± 0.23 lengths s−1, maximum power was 1.47 ± 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
89
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 43 publications
7
89
2
Order By: Relevance
“…4). This may be consistent with the result that a roughly proportional relationship exists between the rate of ATP utilization and the fibre shortening velocity (Reggiani et al, 1997;He et al, 2000;Potma and Stienen, 1996), but not with the biphasic relationship between the rate of energy liberation (heat + work) and the shortening velocity in whole muscle (Hill, 1964;Linari and Woledge, 1995). The approximately linear dependence of the amount of ATP utilized for work production on the distance of shortening (Fig.…”
Section: Relationship With Previous Studiessupporting
confidence: 77%
See 1 more Smart Citation
“…4). This may be consistent with the result that a roughly proportional relationship exists between the rate of ATP utilization and the fibre shortening velocity (Reggiani et al, 1997;He et al, 2000;Potma and Stienen, 1996), but not with the biphasic relationship between the rate of energy liberation (heat + work) and the shortening velocity in whole muscle (Hill, 1964;Linari and Woledge, 1995). The approximately linear dependence of the amount of ATP utilized for work production on the distance of shortening (Fig.…”
Section: Relationship With Previous Studiessupporting
confidence: 77%
“…The maximum mechanical efficiency of Ca 2+ -activated skeletal muscle fibres has been reported to range from 0.2 to 0.46 (He et al, 1997;Reggiani et al, 1997;Sun et al, 2001), indicating that the net maximum mechanical efficiency of cross-bridges during their asynchronous activity is much smaller than the maximum mechanical efficiency of individual cross-bridges obtained in the present study. In this connection, it is of interest that, in demembranated cardiac myocytes, the maximum Ca 2+ -activated isometric force increases by one third when the ATP concentration is reduced to 200 µmol l -1 (Fabiato and Fabiato, 1975).…”
Section: Relationship With Previous Studiescontrasting
confidence: 52%
“…These discrepancies are likely due to the various species, strains, muscles, ages, and techniques to quantitate MHC isoforms that were utilized in the studies. Shortening velocity is influenced by the essential MLC as well, presumably by altering ATPase hydrolysis (Reggiani et al, 1997). Only small age-related isoform shifts in MLC proteins occurred in the myofibril samples.…”
Section: Discussionmentioning
confidence: 99%
“…Widen and Barclay (2006) suggested that the enthalpy output by the mouse papillary muscle was partitioned into force-dependent, and force independent fractions, pointing the importance of the unavoidable additional metabolic energy expense, accompanying the muscle work. The procedure described in this paper is different than that of Reggiani et al (1997), who based their calculations on the free energy change of the ATP hydrolysis, and experimentally determined mechanical work performance.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous experimental and analytical studies are performed to determine the heat released and work produced via muscle contractions since the pioneer work of Hill (Reggiani et al 1997;Holmes, 2006). Energy (either enthalpy or free energy), which is released upon ATP hydrolysis depends on cellular conditions (Alberty 1969;Woledge and Reilly 1988).…”
Section: Comparison Of the Theoretical Limits With The Calculations Bmentioning
confidence: 99%